Peran Media Sosial dalam Membentuk Persepsi Keagamaan di Kalangan Generasi Muda - Asmuni, Hadiqoh; Irawan, Vaesol Wahyu Eka (MOMENTUM : Jurnal Sosial dan Keagamaan, 2025)
This study aims to analyze the role of social media in shaping religious perceptions among the younger generation. Using a literature review approach, data were collected from various relevant written sources such as journals, scholarly articles, and research reports. The findings indicate that social media has become a dominant platform in the daily lives of young people, including in accessing and understanding religious information. Social media enables the widespread and rapid dissemination of religious messages through engaging and interactive digital content. However, it also presents serious challenges, such as the spread of misinformation, the polarization of religious understanding, and the potential rise of intolerance due to perceptions formed without critical thinking. Therefore, strong digital religious literacy and guidance from families and educational institutions are essential to ensure that social media can be utilized positively as a medium for inclusive, moderate, and contextual religious learning. This study contributes theoretically to the discourse on religion and media, while also serving as a practical reference for efforts to strengthen the religious character of youth in the digital era.